Self-stigma and psychosocial burden of patients with port-wine stain: A systematic review and meta-analysis - Rungsima Wanitphakdeedecha (2022)
Background: Port-wine stain (PWS) is a congenital malformation that does not resolve spontaneously and can lead to social and self-stigma. However, little is known about how PWS affects the patients' quality of life (QoL) and psychosocial well-being. In this article, we examine the existing empirical evidence on self-stigma caused by PWS. Methods: A systematic review was done using MEDLINE, PubMed, Embase, and Cochrane databases on January 15, 2021 to retrieve all case reports, cohort studies, and clinical trials written in English. The keywords used in this literature search included port-wine stain, quality of life, self-stigma, and social stigma. Results: From the 74 initial records, eight articles were quantitative studies that assessed the QoL and self-stigma experienced by PWS patients. With regard to perceived stigma or the patients’ understanding of how others think and act toward them, we found that the parents of children with facial PWS tend to have more perceived stigma than the children. For anticipated stigma or expectations of future stigma, young patients with PWS have less or no concern about their skin conditions. In terms of enacted stigma or experiences with discriminatory acts, there were significant differences in the QoL score between patients with facial PWS and those with non-facial PWS. Conclusion: This study suggests that self-stigma caused by PWS affects young patients and their parents. The parents in particular tend to suffer more than their children from perceived and anticipated stigma. Psychological support and early treatment can improve the livelihoods of young patients and their parents.